2020
DOI: 10.1021/acssuschemeng.0c00080
|View full text |Cite
|
Sign up to set email alerts
|

Novel Understanding of Simultaneous Extraction of Vanadium and Manganese from Vanadium Slag and Low-Grade Pyrolusite Based on Selective Oxidation–Reduction Roasting

Abstract: Fresh thinking based on selective oxidation− reduction roasting was proposed to recover vanadium and manganese from vanadium slag (VS) and low-grade pyrolusite (LGP) simultaneously. This approach is inspired by the fact that vanadium (V 3+ ) in VS needs to be oxidized, while manganese (Mn 4+ ) in LGP needs to be reduced. X-ray diffraction (XRD), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS) were performed to analyze the selective oxidation−reduction mechanism of VS and LGP (VS&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Vanadium in vanadium slag reacts with calcification additives to form acid-soluble calcium vanadate to improve the leaching rate of vanadium. 6,12 In recent years, research related to strengthening roasting has been reported, such as the proposed BaCO 3 /CaO composite roasting, 13 MgO/CaO composite roasting, 9 manganese roasting, 14 microwave roasting, 15 and so forth. It is mostly understood and emphasizes the role of roasting vanadium slag from the destruction of the spinel phase structure.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium in vanadium slag reacts with calcification additives to form acid-soluble calcium vanadate to improve the leaching rate of vanadium. 6,12 In recent years, research related to strengthening roasting has been reported, such as the proposed BaCO 3 /CaO composite roasting, 13 MgO/CaO composite roasting, 9 manganese roasting, 14 microwave roasting, 15 and so forth. It is mostly understood and emphasizes the role of roasting vanadium slag from the destruction of the spinel phase structure.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Herein, it is meaningful to explore a short, low production cost and environment-friendly technology for the production of FeV alloy, and producing FeV alloy using VS directly has been caused much attention. [12][13][14] In the past decades, based on the fact that the spinel phase is wrapped by silicate phase in VS, [15,16] a two-step direct reduction to produce FeV alloy using VS was investigated by many researchers to solve the environmental pollution problem of leaching liquor wastewater and further shorten the production routing. [17,18] The first step reduction, namely, prereduction, was the enrichment of vanadium by selective carbothermic or silicothermic reduction of FeO x and other impurities except for V 2 O 3 , satisfying the composition goal of the production of FeV60 alloy (50-65 wt% V).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported either the coextraction, or the solid-state combination of vanadium and manganese in metallurgical contexts. [38][39][40] For this reason, and for reasons which pertain to the results of this thesis, a brief overview of the Mn-V literature is warranted. While not many studies have been conducted into Mn-V systems, there are two categories which is considered: Mn-V alloys, and Mn-V oxides.…”
Section: Vanadium-manganese Chemistrymentioning
confidence: 99%